Randomized controlled trial of a peer led multimodal intervention for men with prostate cancer to increase exercise participation. Issue 1 (27th July 2017) - Galvão, Daniel A.; Newton, Robert U.; Girgis, Afaf; Lepore, Stephen J.; Stiller, Anna; Mihalopoulos, Cathrine; Gardiner, Robert A.; Taaffe, Dennis R.; Occhipinti, Stefano; Chambers, Suzanne K.
Abstract: Objective: Exercise may reduce morbidity, increase survival, and improve quality of life (QoL) in prostate cancer patients. However, effective ways to encourage exercise outside carefully controlled clinical trials remain uncertain. We evaluated the effectiveness of peer‐led self‐management for increasing exercise participation in men with localized prostate cancer. Methods: Four hundred and sixty‐three prostate cancer patients from Queensland, Australia were randomized to a monthly telephone‐based group peer support for 6 months supported by self‐management materials and exercise equipment (INT, n  = 232) or usual care (UC, n  = 231). Participants were assessed at baseline, 3, 6, and 12 months. Primary outcomes were compliance with exercise guidelines; secondary outcomes were psychological distress and QoL. Results: Patients in INT engaged in more resistance exercise than UC at 3 months (19.4 [95% CI 6.52 to 32.28] min/wk, P  = .003) and 6 months (14.6 [95% CI 1.69 to 27.58] min/wk, P  = .027); more men achieved sufficient physical activity levels at 3 months (χ 2  = 8.89, P  = 0.003). There was no difference between groups for aerobic‐based activity at any time point nor for resistance exercise time at 12‐month follow‐up. INT had higher QoL Relationships scores at 3 months (.03 [95% CI .00 to .06], P  = .038) compared with UC. Limitation included self‐reported assessment of exercise. Conclusions: Peer‐led intervention was effective in increasing patients' resistance exercise participation in the short‐to‐medium term and in the number of men achieving sufficient activity levels in the short‐term; however, this was not accompanied by overall improvements in QoL or psychological distress. Methods to increase effectiveness and maintain long‐term adherence require further investigation.